REASONS OF WAIVER OF EXISTENT METHOD FINDING OF TYPE OF SCREW-THREAD LATHE CHISEL FOR MAKING OF BIG SIZE SCREW-THREADS ON PIPES OF OIL AND GAS ASSORTMENT - Онисько, Олег Романович; Бажалук, Назар Романович; Дякун, Павло Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Manufacture of threaded end of pipe oil grades mostly performed by lath threding machin-tools. The current method of thread lathe tool. profiling involves first determining the actual carving a surface, and then due to its intersection with the front surface of the tool its cutting edge profile is found .Because there is non-zero angles accommodation straight cutting edge areas such thread lathe tool is not possible to perform a given Archimedean screw surface..The resulted thread is based on convoluted helicoid. Its axial section depends on the size of the front angle, and the angle of inclination of the cutting edge. These deficiencies result in rejection of the existing methods of thread lathe tool.